1960
DOI: 10.1021/ja01508a042
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Attack of Ozone on Unsaturated Systems. Ozonolyses of Unsymmetrical Derivatives of 1,2-Dibenzoylethylene1

Abstract: VOl. s2The tan solution was examined by visible-ultraviolet spectroscopy and shown to contain 0.99 mmole of tricyanovinyl alcohol ( A, , , 297 mp, B 11,300) and 0.01 mmole of 1,1,2,3,3-pentacyanopropene (Amsx 397 and 414 mp, e 22,600 and 22,-100, respectively).When a solution of 0.81 g. (5.9 mmoles) of tricyanovinyl chloride in 4 ml. of tetrahydrofuran was treated with 2 ml. of water, a rapid (45 seconds) exothermic reaction took place with evolution of carbon dioxide (identified by the white precipitate it ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
1

Year Published

1962
1962
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…According to the resonance hybrid structure of ozone, it can behave either as an electrophilic or nucleophilic reagent in its initial attack [21]. There is a greater possibility of electrophilic attack than nucleophilic attack in the ozonolysis of carbon-carbon unsaturated bonds; however, electrophilic attacks are more common toward carbon-nitrogen double bonds [22,23]. Despite the mechanism, a stoichiomet- ric relationship must exist between ozone and the double bond.…”
Section: Introductionmentioning
confidence: 99%
“…According to the resonance hybrid structure of ozone, it can behave either as an electrophilic or nucleophilic reagent in its initial attack [21]. There is a greater possibility of electrophilic attack than nucleophilic attack in the ozonolysis of carbon-carbon unsaturated bonds; however, electrophilic attacks are more common toward carbon-nitrogen double bonds [22,23]. Despite the mechanism, a stoichiomet- ric relationship must exist between ozone and the double bond.…”
Section: Introductionmentioning
confidence: 99%
“…Bailey's determinations (19) of the direction of cleavage of 1-substituted 1,2-dibenzoylethylenes, made by isolation of the ozonolysis products in the presence of methanol, have indicated that the inductive, rather than the resonance effects, play a role in distributing the proportions of cleavage. Similarly, Keaveney et al (20) have measured the proportions of cleavage of styrene, propenylbenzene, and 2-methyl-propenylbenzene by isolation of the reaction products.…”
mentioning
confidence: 99%
“…In a sequence of concerted 1,3-dipolar cycloaddition and cycloreversion, carbonyl oxides [4] are formed which are captured by internally generated carbonyl compounds in another 1,3-dipolar cycloaddition to yield ozonides. As a result, for unsymmetrical alkenes, substituent rules for the regioselective OÀO splitting in the cycloreversion step have been formulated [5] [6]. There are, however, exceptions from these rules, and the ozonide-forming step may be bypassed due to low dipolarophilicity of the carbonyl intermediate.…”
mentioning
confidence: 99%